Alam Semesta dalam Persepektif Al-Qur’an dan Hadits - sada, Heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Al-Qur'an is a book of guidance. Allah revealed her to explain to the people the things that can not be understood by human reason, as the essence of faith and rituals of the foundations of ethical and legal useful to regulate the social interaction between human beings. The Qur'an also speaks of the universe, which includes everything that is in the heavens and the earth. Even more than a thousand verses that speak of it to prove the power, knowledge, and infinite wisdom of the creator who is capable of creating eliminate and restore the original natural kebentuk keep this feast.               Her light will continue to burn for millions of years without outages, this is a result of the interaction of atoms in the star's known the term "process of fusion of atomic nuclei". Nature is now expanding. If we want to see his origin, should we go back to the past until we find the first material. This material has a very high energy intensity that makes the crisis, the first material that later exploded and turned into clouds of smoke. From the cloud of smoke that God created a vortex that collects a number of matter and energy around the center of gravity (vortex). Collection of materials and energy that accumulates in him until the power of His celestial body formed into multi-faceted.               Big Bang Theory, which by empirical science is regarded as a fact, only a theory. An indication of this is already in the Koran 1400 years ago. This makes the Qur'an as a pioneer of this theory and provides a solid foundation for the Big Bang theory as a fact for their instructions in the Koran. On that basis, the universe was first a solid material (still -bersatu period), then the material is exploded (the period of separation), and then turned into a puff of smoke (smoke period). Scientists empirical claim that nature turns into a cloud of dust, while the Koran says, "Then, he headed to the sky and the (sky) was still in the form of smoke, and He said to it and to the earth, 'Come both of you, according to my commandments with obedient or forced. 'They said,' We came obediently. ' "(Fushshilat: 11).